Dietary starch breakdown product sensing mobilizes and apically activates α‐glucosidases in small intestinal enterocytes. Issue 7 (20th February 2018) - Chegeni, Mohammad; Amiri, Mahdi; Nichols, Buford L.; Nairn, Hassan Y.; Hamaker, Bruce R.
Abstract : Dietary starch is finally converted to glucose for absorption by the small intestine mucosal α ‐glucosidases (sucrase‐isomaltase [SI] and maltase‐glucoamylase), and control of this process has health implications. Here, the molecular mechanisms were analyzed associated with starch‐triggered maturation and transport of SI. Biosynthetic pulse‐chase in Caco‐2 cells revealed that the high MW SI species (265 kDa) induced by maltose (an α ‐amylase starch digestion product) had a higher rate of early trafficking and maturation compared with a glucose‐induced SI (245 kDa). The maltose‐induced SI was found to have higher affinity to lipid rafts, which are associated with enhanced targeting to the apical membrane and higher activity. Accordingly, in situ maltose‐hydrolyzing action was enhanced in the maltose‐treated cells. Thus, starch digestion products at the luminal surface of small intestinal enterocytes are sensed and accelerate the intracellular processing of SI to enhance starch digestion capacity in the intestinal lumen.—Chegeni, M., Amiri, M., Nichols, B. L., Naim, H. Y., Hamaker, B. R. Dietary starch breakdown product sensing mobilizes and apically activates α‐glucosidases in small intestinal enterocytes. FASEB J. 32, 3903–3911 (2018). www.fasebj.org